2013
DOI: 10.1007/978-3-642-38267-3_40
|View full text |Cite
|
Sign up to set email alerts
|

Partial Optimality via Iterative Pruning for the Potts Model

Abstract: Abstract. We propose a novel method to obtain a part of an optimal non-relaxed integral solution for energy minimization problems with Potts interactions, known also as the minimal partition problem. The method empirically outperforms previous approaches like MQPBO and Kovtun's method in most of our test instances and especially in hard ones. As a starting point our approach uses the solution of a commonly accepted convex relaxation of the problem. This solution is then iteratively pruned until our criterion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Recently, Swoboda et al [35] published a new algorithm to obtain partial optimality in Potts models which increases the number of known variables significantly. In future work we will employ this method, consider methods for higher order factors, methods that provide stronger partial optimality criteria, as well as methods for general pairwise terms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Swoboda et al [35] published a new algorithm to obtain partial optimality in Potts models which increases the number of known variables significantly. In future work we will employ this method, consider methods for higher order factors, methods that provide stronger partial optimality criteria, as well as methods for general pairwise terms.…”
Section: Discussionmentioning
confidence: 99%
“…Persistency criteria for the multilabel Potts problem that can be efficiently checked with max-flow computations have been developed in [27,28] and refined in [14]. More powerful criteria based on LP-relaxations have been proposed for the multilabel Potts problem in [41] and in [38,42,40] for general discrete MRFs. An in-depth exposition of the concept of improving mappings that is used implicitly or explicitly for all of the above MRF criteria can be found in [37].…”
Section: Related Workmentioning
confidence: 99%
“…In contrast to the above methods that technically rely either on local conditions or on computing a maximum flow (min-cut), the works [42,43,44] and [35] proposed persistency approaches relying on a general linear programming relaxation. Authors of [42,43,44] demonstrated applicability of their approach to large-scale problems by utilizing existing efficient approximate MAP-inference algorithms, while in [35] the large-scale problems are addressed using a windowing technique. Despite the superior persistency results, the running time of the approximate-LP-based methods remained prohibitively slow for practical applications as illustrated by an example in Fig.…”
Section: Related Workmentioning
confidence: 99%
“…There are only two possible choices for p v : either i → y v for all i ∈ X v or the identity i → i. Methods [24,42,43] can be explained as finding an improving mapping in this class [35]. We generalize the method [43] to substitutions in P 2,y .…”
Section: Comparison To Previous Workmentioning
confidence: 99%